Virological Failure and Drug Resistance in Patients on Antiretroviral Therapy After Treatment Interruption in Lilongwe, Malawi - Lübbert, Julia; Ramroth, Heribert; Schnitzler, Paul; Neuhann, Florian (Clinical infectious diseases, 2012)
Virological failure to first-line antiretroviral therapy (ART) due to nonnucleoside reverse transcriptase inhibitor/nucleoside reverse transcriptase inhibitor m